Práticas educativas na educação infantil: um olhar a partir do estágio supervisionado em uma escola municipal de Augusto Corrêa/PA. - AMORIM, Edinei Lisboa (2023)
This experience report discusses the supervised internship and was motivated by the following guiding questions: What role does the supervised internship in Early Childhood Education play in training professionals who work with children from 0 to 5 years of age? How to organize a pedagogical practice based on space and time so that these children can build and appropriate the cultural assets of humanity? It aims to present reflections produced on the experiences observed and constructed at the time of the development of the Supervised Internship in Early Childhood Education, which took place from 10/20/2021 to 11/08/2021, in a public school in the municipality of Augusto Corrêa - Pará. As a methodology, it uses the qualitative approach as an instrument of data collection observation, and records in the field notebook. The results demonstrate that the internship enabled the deepening and construction of important theoretical and practical references for teacher training from the perspective of their performance in the first stage of basic education.